Determinan Financial Distress pada Masa Kompensasi Kerugian Fiskal - Novita Wardani; Muhammad Abdul Aris (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to analyze the Determinants of Financial Distress during the Fiscal Loss Compensation Period (Empirical Study of Manufacturing Companies Listed on the Indonesian Stock Exchange for the 2020-2023 Period). This research uses secondary data obtained from the company's annual financial reports. The sampling technique used in this research was purposive sampling. A total of 36 companies have met the criteria as observation units. The analytical methods used include descriptive statistics and multiple linear regression. The results of this research indicate that the variables Profitability, Liquidity and Operating Cash Flow have an influence on Financial Distress. Meanwhile, the Leverage variable has no influence on Financial Distress.